Punctuating Proficiency on Writing Skill by The Sophomore Students of The English Educational Study Program UPG 1945 NTT in Academic Year 2024/2025: English - Buifena , Zipora Niti; Anabokay , Yanrini Martha; Sekoni, Rocky Paulus; Langkameng, Oce Antipas (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The primary aim is to assess students' understanding and application of punctuation rules while identifying common challenges faced in their writing. Employing a qualitative methods approach, data were gathered through writing samples and surveys to provide a comprehensive evaluation of punctuation skills. Findings reveal varying levels of proficiency, with notable difficulties in fundamental punctuation rules that adversely impact overall writing quality. The analysis highlights patterns of struggle and the effectiveness of current instructional practices. The discussion emphasizes the need for targeted pedagogical strategies to address these gaps, advocating for practical exercises and personalized feedback in the curriculum. Overall, this research contributes valuable insights into punctuation proficiency, offering recommendations to enhance writing skills and instructional methods, ultimately shaping competent future educators and enriching the educational experience.